Combined deficiency of iron and vitamin D in Asian toddlers. Issue 9 (September 1986) - Grindulis, H; Scott, P H; Belton, N R; Wharton, B A
Abstract : One hundred and forty five Asian children born at Sorrento Maternity Hospital, Birmingham, were reviewed at the age of 22 months. A significant association of iron deficiency and poor vitamin D state was found. Two fifths of the children were anaemic, two fifths had a low plasma concentration of vitamin D, and one fifth had both features. This was more than simple overlap of the two deficiencies; the children with low plasma vitamin D concentrations had significantly lower concentrations of haemoglobin and serum iron. On the other hand, the deficiencies were not merely individual features of generally poor nutrition; growth and other measures of protein energy nutrition were slightly better in these children, and their plasma zinc concentration was no lower than in the children without deficiencies. It seems, therefore, that child health surveillance as currently practised--for example, growth monitoring, clinical signs, etc--will not detect these problems unless a haemoglobin determination is included. In view of the association of poor iron and vitamin D state combined prophylaxis is desirable. At present, strategies for preventing rickets in this country are not combined with attempts to detect or prevent iron deficiency. In our opinion they should be and the options are discussed.